Revolution in Project Management: Focusing on Sustainability and AI - Székely, Blanka; Késmárki-Gally, Szilvia Erdeiné (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
In recent years, sustainability has become a pivotal focus in several areas, including project management, driven by the need to address environmental, social, and governance (ESG) considerations. This journal explores the integration possibilities and practices of sustainability in project management, emphasizing the role of Industry 5.0 and artificial intelligence (AI) in enhancing ESG outcomes through a systematic literature review of currently accessible academic literature. This literature review, following PRISMA guidelines, addresses 4 research questions. Findings reveal a scarcity of relevant literature, indicating lack of popularity among researchers. Industry 5.0, characterized by the collaboration between humans and advanced technologies, offers a transformative approach to project management by fostering innovation and sustainability. AI, with its capabilities in data analysis, predictive modelling, and decision support, plays a crucial role in supporting ESG initiatives. By leveraging AI, project managers can ensure that projects align with sustainability goals, optimize resource utilization, and enhance transparency and accountability. The authors dive into the synergies between Industry 5.0’s pillars and AI, highlighting their potential to drive sustainable project management practices and contribute to long-term value creation for organizations.